Assessment of Land Damage for Biomass Production - Suhermi, Helnita; Umar, Iswandi; Dewata, Indang; Carlo, Nasfryzal (European Journal of Life Safety and Stability (2660-9630), 2022)
Padang City is the center of growth for the province of West Sumatra, with an area of 694.96 km2 with a population of Padang City reaching 913448 people in 2021. Padang City is planned to utilize space with the development of a harmonious area between settlements, socio-economic activities, and efforts conservation. The rapid population growth and regional development will also have implications for land needs. One of the potential developments of the Padang City area when viewed from the economic activity of the agricultural potential area. Continuous use of land can result in land damage. This study aims to determine the status of land damage and its limiting factors. The method used in the research is the survey method, through direct observation and soil sampling in the field, followed by laboratory analysis. Parameters of soil damage and sampling procedures are guided by Government Regulation No. 150/2000 and Regulation of the Minister of the Environment No. 7/2006. Based on laboratory data analysis, the status of land damage can be determined by using the matching method and scoring the weight of each parameter on the entire sample point, so that based on The results of laboratory analysis show that Padang City has a level of land damage, with a moderate damage index (38-59), with two limiting parameters for soil damage factors, namely; redox and Electrical Conductivity (DHL).